Architectural Design Methods According to Advance Human's Intellect & Technology - Ahmed Talib Hameed Haddad (Iraqi Journal of Architecture and Planning, 2018)
This paper explain design method as a ring or relationship link between theory and applied , and it discuss the important developments in the field of architectural design methods according to advance human's intellect & his technology ; firstly from intuition thinking ( according to try and error ) to the industrial revolution that is followed mathematical and rational limitation thinking , and this thought go directly to un-limitation thinking that’s followed new scientific revolution , and it is arrive to contemporary digital revolution . Beside this that paper search for a development relationship between architectural form and architectural design methods .Finally must be recommendation how to effect this important development in design methods and tools on the task of teach architectural design.